NEP (Children@School): An instrument for measuring environmental attitudes in middle childhood - Izadpanahi, Parisa; Tucker, R. (Australian Association for Environmental Education Inc., 2018)
While there are many environmental education programs for children, few studies have used an appropriately developed scale for evaluating how such education might have on impact on children's environmental orientations. The research presented in this article adapted the NEP (New Ecological Paradigm) for Children scale to develop a new instrument for measuring children's environmental attitudes: The NEP (Children@School). The NEP (Children@School) has been developed by analysing the impact of the design of physical learning spaces on children's environmental attitudes. Factor analysis indicated that NEP (Children@School) has three dimensions: Children's Environmental Attitudes towards Human Intervention, Children's Environmental Attitudes via ESD at School, and Children's Environmental Attitudes towards Eco-Rights. We argue that NEP (Children@School) can meaningfully measure the impact of learning spaces on children's environmental attitudes. While the instrument was developed for use in Australia, it has been designed for global applicability.